Participation of the Armed Forces in National Development - Sanchez Chavez, Luis Alberto (2020)
The participation of the Armed Forces in National Development helps other sectors with the use of their capabilities, mainly with the use of their human and material resources, in order to achieve the fulfillment of their objectives, especially in those places where the presence and State participation is scarce or nil due to the rugged geography. Thus, the objective of this research work is to know the way in which the Armed Forces of Peru participate in National Development. An exploratory investigation was implemented as a methodology, based on previously performed work, interviews with experts, knowledge of reality, articles and information related to the topic, identifying the way in which the Peruvian Armed Forces participate in National Development and then After performing an analysis, submit an alternative proposal. Finally, it was concluded that Currently, the Armed Forces in Peru continue to play the traditional role established by the Political Constitution of Peru and, only temporarily participate at the request of the political authority in cases of emergencies produced as a result of the action of the natural phenomena and specific tasks, for which the corresponding legal instruments have been implemented. However, additionally, the Armed Forces have developed initiatives to be able to have some degree of participation in national development, some of which are already in a state of operation, others in a state of implementation or project.